ANALISIS PENGARUH LOYALTY, PERSEPSI HARGA DAN TRUST TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Resya, Fachmi; Andriyanto, Dicky; Mayasari, Financia; Alam Wiguna, Ardhitya; Yuniar, Eka (Universitas Islam Balitar, 2025)
This research aims to determine the influence of loyalty, price pereception and consumer trust on purchasing decisions. This research was conducted by analyzing loyalty, price pereception, and trust variables on consumer purchasing decisions at Kedai Ndalung. Sampling was carried out using a non-probability sampling technique with a total of 40 respondents. The analytical tool in this research uses multiple linear regression analysis based on SPSS 21. The results of this research conclude that the variables loyalty(X1), price pereception(X2), and trust(X3) simultaneously have a significant effect on consumer purchasing decisions (Y). Partially from the results of this research, it can be concluded that the loyalty(X1), and trust (X3) has a positive and significant effect on consumers' purchasing decisions (Y), while the variables price pereception (X2) have a positive and insignificant effect on consumers' purchasing decisions (Y).